The faith of graffiti - Mailer, Norman 1923-2007 (ItBooks, 2009)
A fearless exploration of the birth of the street art movement in New York City, this new edition of "The Faith of Graffiti" is enhanced with thirty-two pages of additional photographs and an afterword in which Naar reflects on the project and the meaning it has taken on in the intervening decades